The Role of Employee Involvement and Psychological Empowerment on Employees' Workforce Agility at PT. XYZ Telecommunication Industry: Intervention Program “Agile Empower” - Alqumairah, Andi Aisyah; Purba, Debora Eflina (International Journal of Science and Society, 2024)
Organizational changes such as mergers and acquisitions, evolving customer demands, and increasing business competition in the telecommunications industry require employees of PT. XYZ to work agilely to adapt and implement changes in uncertain conditions. This study aims to examine the role of employee involvement and psychological empowerment in influencing workforce agility among employees at PT. XYZ. A total of 251 permanent employees at the headquarters participated in this research. The measurement tools used were the Workforce Agility Questionnaire (WAQ) by Sherehiy et al. (2014), translated into Indonesian by Alavi (2016); the Employee Involvement Questionnaire (EIQ) by Lawyer (1992), translated into Indonesian by Heckscher (2018); and the Psychological Empowerment Questionnaire (PEQ) by Spreitzer (1995), translated by Aam Amaliah & Laila (2021). The results showed a significant relationship between employee involvement and workforce agility (r = 0.460, p < 0.05), as well as between psychological empowerment and workforce agility (r = 0.680, p < 0.05). Multiple linear regression analysis revealed that employee involvement contributed 21% (Standard Estimate = 0.201, p < 0.05) and psychological empowerment contributed 59% (Standard Estimate = 0.593, p < 0.05) to workforce agility. Based on these findings, an Agile Empower intervention was conducted with 26 participants who scored low to moderate in psychological empowerment. Post-intervention evaluation showed a significant improvement in pretest and post-test scores, with a mean difference (p < 0.05) and an implementation evaluation score of 3.7 out of 4.0.